C Catch Per Unit Effort (CPUE) Rhynchobatus sp Menggunakan Gill Net Dasar Di Wilayah Pengelolaan Perikanan 711 (WPP NRI 711) Pada Fishing Base PPI Sungai Kakap Kalimantan Barat - sadri sadri; Frangky Fransiskus Tumion; Jumadi Sudarso; Rahmat Muallim (Jurnal Kelautan, Lingkungan, dan Perikanan, 2021)
Rhynchobatus springeri (R. springeri) and Rhynchobatus australiae (R. australiae), which belong to wedgefish species, are the main target of captures of the bottom gill net fishery at PPI Sungai Kakap, West Kalimantan, a fishing ground in the Indonesian Fisheries Management Area 711 (WPP NRI 711). The fin is the main part in business activity in fisheries and has been exported due to high demand with promising price. But, there is a scarcity of research on this species (Jabado, 2019) especially the information about the level of vulnerability of the wedgefish species. The status of R. springeri and R. australiae are critically endangered on the International Union for Conservation of Nature (IUCN) Red List (Jabado, 2019; Kyne, 2019; Kyne et al, 2019a; IUCN, 2012). CPUE is the amount of fish catch per unit of effort. The term ‘effort’ in this research is the length of days at sea per trip of fishing operation. Data collection includes the number of landings of Rhynchobatus species and length of days at sea from each fishing vessel during the years of 2016 and 2019. Microsoft Excel was used for data analysis. The results showed that the average CPUE was 54.34 piece/trip, or 1,512.19 kg/trip and 1.75 piece/day, or 48.78 kg/day per ship. The correlation between CPUE and effort is positively significant. At the CPUE piece/trip, the linear equation shown as follow y = 0.3583x-38.531 with R2 = 0.8724 or R = 0.9340. Whereas, at the CPUE kg/trip, the linear equation was y = 9,0823x-842,11 with R2 = 0,791 or R = 0,889 (Y is CPUE and X is effort).